Technical efficiency in Brazilian manufacturing establishments: Results for 1970 and 1980 - Armando Castelar Pinheiro (Institute for Applied Economic Research (ipea), 2015)
The objective of this paper is to identify variables that influenced the efficiency level of Brazilian manufacturing establishments in 1970 and 1980. Efficiency is defined as the ratio of actual to best practice output, which is measured using deterministic translog frontier production functions. Maximum likelihood estimators are obtained for each sector. Thirteen variables are examined, with trade orientation and, especially, industrial structure showing to be significantly associated with efficiency.
Keywords: 330